Analysis of the effects of control strategies and wave climates on the loading and performance of a laboratory scale horizontal axis tidal turbine. (15th September 2020) - Martinez, Rodrigo; Ordonez-Sanchez, Stephanie; Allmark, Matthew; Lloyd, Catherine; O'Doherty, Tim; Germain, Gregory; Gaurier, Benoit; Johnstone, Cameron
Abstract: To understand the influence of complex hydrodynamic loads on tidal turbines, laboratory testing is necessary as a first approach. Previous laboratory work undertaken gave an indication that the use of speed control strategies may disguise the associated loading range that a turbine may be subjected to when this is operated with a variable speed control strategy. However, the preceding work was undertaken in a highly controlled environment without the influence of turbulent flows. The focus of this paper is directed towards the study of wave-induced loads on tidal turbines when these are controlled using two strategies and the impact that these parameters have on the turbine's performance when this is operated in a recirculating flume. Laboratory tests were undertaken with a 0.9 m diameter horizontal axis tidal turbine subjected to combined wave and current conditions with both regular and irregular waves. Constant speed and constant torque control strategies have been considered, for which rotor thrust, torque and blade root bending moment have been measured. Results show that similar to previous studies, average loads and power capture values remain unchanged between control strategies and the superposition of waves to the current. However, signal fluctuations are 2 to 3 times higher for torque control than for constant speed control strategy. A phase difference between the periodic signals of the turbine thrust and the incoming waves was also identified, in this case, the phase variation was lower when using torque than speed control. This work thus demonstrates the implication of studying strategies to control a marine converter from early stages of development. Highlights: Recirculating tank testing demonstrated the loading and performance effects when using two control methodologies. Thrust, torque and root bending moment fluctuations are higher when using torque control than speed control. Phase differences between the periodic signals of the turbine thrust and the incoming waves is analysed. The effect of combined turbulent flows and regular and irregular wave interaction is presented.